Predictive value of the neutrophil-to-lymphocyte ratio for treatment response in patients diagnosed with definite or probable autoimmune encephalitis/encephalopathy - Ogami, Shuhei; Koh, Jinsoo; Miyamoto, Katsuichi; Mori, Megumi; Takahashi, Maiko; Nakayama, Yoshiaki; Sakata, Mayumi; Hiwatani, Yasuhiro; Kajimoto, Yoshinori; Ishiguchi, Hiroshi; Ito, Hidefumi (Frontiers in Neurology, 2023)
Introduction Autoimmune encephalitis/encephalopathy (AE) is a complex and heterogeneous disease, making it difficult to predict the prognosis. The neutrophil-to-lymphocyte ratio (NLR) has emerged as a potential prognostic tool, but its usefulness remains a matter of debate. This study aimed to explore prognostic factors in cases of clinically definite or probable AE, including those with autoantibody-negative, or unknown status. Methods Data on patients diagnosed with definite or probable AE, including those with autoantibody-negative, or unknown status, were retrospectively collected from the admission records of our department between January 2013 and December 2022. These patients were then categorized into either a good- or poor-response group, based on their short-term treatment response. Clinical characteristics, auxiliary examinations, and treatments were compared between the two groups. A multivariable logistic regression model was constructed to identify independent predictors of poor short-term treatment response by Akaike information criterion backward stepwise method. Results A total of 31 patients were included in the final analysis, with 18 of them included in the poor-response group. In the univariable analysis, the poor-response group had a higher proportion of patients with a modified Rankin Scale (mRS) high score upon admission, female, epileptic seizures, or NLRs of 3.93 or higher than the good-response group (all p < 0.10). Furthermore, the multivariable logistic regression analysis revealed that the mRS score upon admission [OR: 5.51, 95% confidence intervals (CI): 1.29–23.50, p = 0.02], epileptic seizures (OR: 10.01, 95% CI: 1.16–86.66, p = 0.04), and NLRs of 3.93 or higher (OR: 11.37, 95% CI: 1.12–114.68, p = 0.04) were significantly associated with poor short-term treatment response. Conclusion The NLR may play a supplementary role in predicting the short-term treatment response in patients diagnosed with definite or probable AE, including those with autoantibody-negative, or unknown status.